Be X-ray binaries in the SMC as indicators of mass-transfer efficiency. Issue 4 (4th September 2020) - Vinciguerra, Serena; Neijssel, Coenraad J; Vigna-Gómez, Alejandro; Mandel, Ilya; Podsiadlowski, Philipp; Maccarone, Thomas J; Nicholl, Matt; Kingdon, Samuel; Perry, Alice; Salemi, Francesco
ABSTRACT: Be X-ray binaries (BeXRBs) consist of rapidly rotating Be stars with neutron star (NS) companions accreting from the circumstellar emission disc. We compare the observed population of BeXRBs in the Small Magellanic Cloud (SMC) with simulated populations of BeXRB-like systems produced with the compas population synthesis code. We focus on the apparently higher minimal mass of Be stars in BeXRBs than in the Be population at large. Assuming that BeXRBs experienced only dynamically stable mass transfer, their mass distribution suggests that at least 30 per cent of the mass donated by the progenitor of the NS is typically accreted by the B-star companion. We expect these results to affect predictions for the population of double compact object mergers. A convolution of the simulated BeXRB population with the star formation history of the SMC shows that the excess of BeXRBs is most likely explained by this galaxy's burst of star formation ∼20–40 Myr ago.